Further labdane and kaurane diterpenoids and other constituents from Plectranthus fruticosus - Gaspar-Marques, C (2015)
Eight new diterpenoids, one labdane and seven kaurane derivatives, and a new aromadendrane-type sesquiterpenoid have been isolated from the most polar chromatographic fractions of an acetone extract of Plectranthus fruticosus. The structures of the new compounds (1-9) were established mainly by ID and 2D NMR studies and by some chemical transformations. Compounds 6 and 8 were characterized as their methyl ester derivatives (13 and 14, respectively). Most of the isolated compounds and some of their derivatives were tested as antimicrobial agents, but only 19 showed moderate inhibitory activity against Staphylococcus aureus.